2020
DOI: 10.3390/ijerph17030698
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Mycotoxin Exposure and Dietary Habits in Colorectal Cancer Development Among a Polish Population: A Study Protocol

Abstract: Colorectal cancer (CRC) is one of the most common and lethal types of cancer worldwide. The developing of this disease includes many factors such as genetic, socioeconomic, environmental, and lifestyle factors, and nutrition habits. The aim of the study is the determination of zearalenone and its metabolite level in the biological samples of participants at risk of CRC, in relation to the nutrition data and information on the quality of life dependent on health. In the cohort clinical trial, 150 participants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…These studies have reported that aflatoxins (especially aflatoxin B1) may pose a carcinogenic risk and exposure to these chemicals may increase the risk of gastric and colorectal cancer [ 259 , 260 ]. Other studies suggest a correlation between the exposure to ZEN and colorectal cancer [ 261 ], as well as relationships between exposure to aflatoxins and Crohn’s Disease, coeliac disease and ulcerative colitis [ 262 ]. Despite this, differences in concentration of patulin and citrinin in plasma and urine between healthy people and patients suffering from colorectal cancer have not been observed, which may suggest that these mycotoxins are not key factors leading to this disease [ 263 ].…”
Section: Mycotoxin Consumption and Human Gastrointestinal Diseasesmentioning
confidence: 99%
“…These studies have reported that aflatoxins (especially aflatoxin B1) may pose a carcinogenic risk and exposure to these chemicals may increase the risk of gastric and colorectal cancer [ 259 , 260 ]. Other studies suggest a correlation between the exposure to ZEN and colorectal cancer [ 261 ], as well as relationships between exposure to aflatoxins and Crohn’s Disease, coeliac disease and ulcerative colitis [ 262 ]. Despite this, differences in concentration of patulin and citrinin in plasma and urine between healthy people and patients suffering from colorectal cancer have not been observed, which may suggest that these mycotoxins are not key factors leading to this disease [ 263 ].…”
Section: Mycotoxin Consumption and Human Gastrointestinal Diseasesmentioning
confidence: 99%
“…Cereals such as maize, oat, and wheat are considered the most susceptible to mycotoxin contamination [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. It was proven that 25% of cereals consumed in the world in 1988 were contaminated by mycotoxins [ 60 ].…”
Section: Introductionmentioning
confidence: 99%